Phenotypic characterization of Cashmere goats in Western Mongolia (Mongolian Journal of Agricultural Sciences, 2021)
This study was conducted as a preliminary study to design the breeding activity of Mongolian cashmere goats. To characterize the phenotypic traits of goats in Western Mongolia, the linear body measurements and cashmere yield and its the quality were measured. In this study, 608 cashmere goats were selected from the areas where it highly affected to overgrazing and overstocked in this area. The study used a random sampling method from the populations. The normality of the data was checked using the Shapiro-Wilk normality test and analyzed using the linear model procedure in R software. All male (buck) and female goats had straight head profiles (100%). Black coat color was predominant in Erdeneburen, Bayan-Uul soums and all of the goats in Ulgii soum were red. The goats in Ulgii soum were the biggest in body size compared to Erdeneburen and Bayan-Uul in Ulgii soums. The goats had back horn orientation (100%). Significant effects (p